Religious ideology in American politics: a history - Froger-Guétin, Nicole (McFarland, 2009)
"By looking at writings of American thinkers, the work argues for the consistency and permanence of the American religious vision. Manifest Destiny, America as 'God's Country' and Americans as 'God's People' are explored, as is how these ideals of American exceptionalism and the 'City on the Hill' have survived and mutated into the current U.S. political climate"--Provided by publisher